2023
DOI: 10.3390/su151310399
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Spatial-Temporal Changes and Driving Forces of Desertification in the Mu Us Sandy Land from 1991 to 2021

Abstract: Desertification is one of the most critical environmental and socioeconomic issues in the world today. Located in the transitional region between the desert and the Loess Plateau, the Mu Us Sandy Land is one of the nine most environmentally sensitive areas in the world. Remote sensing provides an effective technical method for desertification monitoring. In order to analyze the spatiotemporal distribution of desertification in the Mu Us Sandy Land from 1991 to 2021, the “MSAVI-Albedo” model was employed to ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…The area of the DBSL lakes showed an increasing-decreasing-slowing and continuous decreasing trend from 1980 to 2022, which is consistent with the results obtained by Chen et al [68]. Ji et al [69] analyzed the change law of vegetation in the wind-sand area by combining climate and social factors and found that precipitation is the main climatic factor affecting vegetation change, but the quantitative results show that human activities are an important driving force for vegetation change [70][71][72]. With an increasing population, the demand for food is also increasing, and the area of urban construction land is expanding.…”
Section: Driving Mechanism Of Vegetation-lake-sand Landscape Evolutionsupporting
confidence: 91%
“…The area of the DBSL lakes showed an increasing-decreasing-slowing and continuous decreasing trend from 1980 to 2022, which is consistent with the results obtained by Chen et al [68]. Ji et al [69] analyzed the change law of vegetation in the wind-sand area by combining climate and social factors and found that precipitation is the main climatic factor affecting vegetation change, but the quantitative results show that human activities are an important driving force for vegetation change [70][71][72]. With an increasing population, the demand for food is also increasing, and the area of urban construction land is expanding.…”
Section: Driving Mechanism Of Vegetation-lake-sand Landscape Evolutionsupporting
confidence: 91%
“…Duan et al [18] utilized high-resolution temporal continuous MODIS remote sensing data to focus on the dynamic changes in Horqin Sandy Land from 2000 to 2015. Various studies have demonstrated that the remote sensing index serves as an important indicator for monitoring dynamic changes in sandy lands through remote sensing [6,12,13,16,[19][20][21][22][23][24][25][26][27], and remote sensing data monitoring methods have become the primary approach for monitoring the characteristics of sandy land changes. However, owing to the influence of NDVI changes on the FVC, which is affected by meteorological conditions, there may be some randomness in the dynamic characteristics of sand changes during isolated years (such as a sudden increase in precipitation in the sand area that year, leading to a contraction in the area of sand monitored by the FVC).…”
Section: Introductionmentioning
confidence: 99%